Determinación analítica por exposición a cianuro libre en efluentes mineros, planta artesanal poderosa Ananea – Puno - Argota Pérez, George (2017)
The objective of the research was to determine the ex-position to free cyanide on mining effluents correspon-ding to the Craft Facility Poderosa Ananea, in Puno. In order to do these, we sampled effluents both in high and low rain periods, choosing four representative samples and establishing tree replies. The analytical determina-tion of free cyanide was obtained using the silver ni-trate method. It was observed that among the average values (0.13 and 0.14) of free cyanide (ppm) there were no significant (p<0.05) statistical differences, being those values superior to the maximum values allowed by current regulations. We concluded that the mining effluents were being poured with considerable exposi-tions to free cyanide.